Rok 1989 – wokół pojęcia modernizmu - Włodarczyk, Wojciech (Artium Quaestiones, 2019)
The author argues that the significance of the year 1989 for Polish art was not determined by political changes, but by the rise of postmodernism. Until that moment, the term “modernism” usually referred in academic art history to Polish art at the turn of the 20th century. The concept of postmodernism brought to the Polish language a new meaning of modernism as simply modern art, and more precisely, as modern art defined by Clement Greenberg. That change made it necessary to draw a new map of concepts referring to modern Polish art, most often defined before by the concept of the avant-garde. In Mieczysław Porębski’s essay “Two Programs” [Dwa programy] (1949), and then, since the late 1960s, in Andrzej Turowski’s publications, the concept of the avant-garde was acknowledged as basic for understanding twentieth-century Polish art. The significance of the concept of the avant-garde in reference to the art of the past century in Poland changed after the publication of Piotr Piotrowski’s book of 1999, Meanings of Modernism [Znaczenia modernizmu]. Piotrowski challenged in it the key role of that concept – e.g., Władysław Strzemiński and Henryk Stażewski, usually called avant-gardists before, were considered by him modernists – in favor of a new term, “critical art,” referring to the developments in the 1990. In fact, critical art continued the political heritage of the avant-garde as the radical art of resistance. The author believes that such a set of terms and their meanings imposes on the concept of the avant-garde some limits, as well as suggests that scholars and critics use them rather inconsistently. He argues that concepts should not be treated as just label terms, but they must refer to deeper significance of tendencies in art. He mentions Elżbieta Grabska’s term “realism,” also present in the tradition of studies on modern Polish art, and concludes with a postulate of urgent revision of the relevant vocabulary of Polish art history.